2023
DOI: 10.1002/mnfr.202200735
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol Exerts Protective Effects against Chronic Sleep Deprivation‐Induced Cognitive Impairment via Activation SIRT1/Nrf2 Pathway in the Hippocampi of Adult Mice

Abstract: Scope: Sleep deprivation (SD) negatively affects all aspects of health, with one serious consequence being impaired cognition. Farnesol (FOL) is a sesquiterpene synthesized by plants and mammals that has antioxidant, anti-inflammatory, and neuroprotective properties. This study investigates the mechanism underlying the neuroprotective effect of FOL on SD-induced cognitive impairment. Methods and results: Administration of FOL dramatically ameliorates chronic sleep deprivation (CSD)-induced cognitive impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Activating the Nrf2/HO-1 pathway is emerging as a promising strategy to counteract cognitive impairments induced by sleep deprivation. 100 Nicotinamide adenine dinucleotide phosphate hydrogen oxidase (NOX), an enzyme critical in ROS generation, shows increased expression in the hippocampus and cortex following fragmented sleep, resulting in an excess of ROS and promoting the development of POCD. 101,102 This elevation results in an overproduction of ROS, contributing to the development of POCD.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Activating the Nrf2/HO-1 pathway is emerging as a promising strategy to counteract cognitive impairments induced by sleep deprivation. 100 Nicotinamide adenine dinucleotide phosphate hydrogen oxidase (NOX), an enzyme critical in ROS generation, shows increased expression in the hippocampus and cortex following fragmented sleep, resulting in an excess of ROS and promoting the development of POCD. 101,102 This elevation results in an overproduction of ROS, contributing to the development of POCD.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Farnesol, a natural sesquiterpenoid, exerts neuroprotective effects against sleep deprivation-induced cognitive impairment by activating the SIRT1/NRF2 signaling pathway. Administration of farnesol after chronic sleep deprivation also increases the expressions of HO-1 and GPx in the hippocampi (Li et al 2023b ). Another study indicated that a ketogenic diet, which results in elevated levels of ketones (e.g., β-hydroxybutyrate) in the blood, could prevent sleep deprivation-induced Alzheimer’s disease (AD) by inhibiting ferroptosis, and lipid peroxidation, and improving the neuronal repair ability via SIRT1/NRF2 signaling pathway (Yang et al 2022 ).…”
Section: Modulation Of Nrf2 In Sleep Disruptionmentioning
confidence: 99%
“…Agonists of the α7 nicotinic acetylcholine receptor can activate downstream PI3K/Akt/GSK-3β, restrain the increase of pro-inflammatory factors, and stabilize the expression of anti-inflammatory factors, transcriptor Nrf-2, and antioxidant enzyme HO-1 after SD ( Xue et al, 2019 ). Farnesol, Caffeine and Modafinil can ameliorate SD-induced neuroinflammation and microglial activation ( Wadhwa et al, 2018 ; Li Y. et al, 2023 ). Sinomenine, or cocculine, is an alkaloid found in the root of the climbing plant Sinomenium acutum, which is now considered a beneficial treatment target for CNS diseases such as AD, PD, depression, TBI, epilepsy, multiple sclerosis, cerebral ischemia, and intracerebral hemorrhage ( Hong et al, 2022 ).…”
Section: Potential Interventions Targeting Astrocytes To Prevent or T...mentioning
confidence: 99%